2019
DOI: 10.1111/rda.13521
|View full text |Cite
|
Sign up to set email alerts
|

Biological and biochemical characteristics of male reproductive system, serum metabolites and carcass quality of Japanese quails by the supplementation of Pinus ponderosa leaves and α‐tocopherol acetate

Abstract: The aim of the current study was to evaluate the effect of dietary supplementation of Pinus ponderosa leaves (pine leaves) and α‐tocopherol acetate (vitamin E) powder on male reproductive system, serum metabolites and carcass characteristics of Japanese quails. A total of 360‐day‐old male quails were purchased from the open market and kept at poultry shed for ninety‐four days. After ten days of adaptation, all quails were randomly assigned into 4 groups, control (IC); supplemented with α‐tocopherol acetate (IE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Nowadays, many researchers using several dietary nutritional supplements in animals feed to develop the meat quality, such as vitamin E, sodium selenite, selenium yeast, oats, essential oils of oregano, fermented wheat powder and probiotics strain, for example L. plantarum and P. acidilactici (Casamassima et al, ; Shah et al, ; Simonová, Szabóová, et al, ). Probiotics are living micro‐organisms that develop the digestive system of animals, when they are added in feed (Khan, Javed, & Muhammad, ; Simonová, Lauková, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many researchers using several dietary nutritional supplements in animals feed to develop the meat quality, such as vitamin E, sodium selenite, selenium yeast, oats, essential oils of oregano, fermented wheat powder and probiotics strain, for example L. plantarum and P. acidilactici (Casamassima et al, ; Shah et al, ; Simonová, Szabóová, et al, ). Probiotics are living micro‐organisms that develop the digestive system of animals, when they are added in feed (Khan, Javed, & Muhammad, ; Simonová, Lauková, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that a dose of up to 0.05% MeP is safe to use as a natural feed additive for broilers. Another study reported that the supplementation of pine needles and vitamin E powder in feed improved the performance of female Japanese quail (Khan et al, 2019) but Pinus ponderosa leaf supplementation in Japanese quail feed did not affect performance (Shah et al, 2019). This indicates that not all plant bioactive substances can improve performance.…”
Section: Resultsmentioning
confidence: 99%